2017
DOI: 10.1177/0263617417693626
|View full text |Cite
|
Sign up to set email alerts
|

Development of low-cost iron mixed porous pellet adsorbent by mixture design approach and its application for arsenate and arsenite adsorption from water

Abstract: In this study, natural clay, iron oxide, and iron powder were combined to develop low-cost iron mixed porous pellet adsorbent for arsenate and arsenite removal from aqueous solution in batch experiments. The augmented simplex centroid mixture design was applied to obtain the optimum proportion of each constituent. Higher correlation coefficient of the models (R 2 > 0.95), good distribution of residuals, and lower values of p value (<0.05) indicated that the method is suitable for determining the optimum mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…However, reports showed that traditional carbons could not remove As and F due to its lower adsorption capacity (Rojas‐Mayorga, Bonilla‐Petriciolet, Silvestre‐Albero, Aguayo‐Villarreal, & Mendoza‐Castillo, ; Velazquez‐Jimenez, Arcibar‐Orozco, & Rangel‐Mendez, ). Adsorbent functionalized with aluminum, cerium, lanthanum and zirconium are more capable of removing contaminants (He et al, ; Lin, Wu, Khayambashi, Wang, & Wei, ; Te, Wichitsathian, Yossapol, & Wonglertarak, ). Some special characteristics such as surface area, porosity and the presence of functional groups enhanced the adsorption properties (Arcibar‐Orozco, Josue, Rios‐Hurtado, & Rangel‐Mendez, ).…”
Section: Removal Of Arsenic and Fluoride From Contaminated Water/raw mentioning
confidence: 99%
“…However, reports showed that traditional carbons could not remove As and F due to its lower adsorption capacity (Rojas‐Mayorga, Bonilla‐Petriciolet, Silvestre‐Albero, Aguayo‐Villarreal, & Mendoza‐Castillo, ; Velazquez‐Jimenez, Arcibar‐Orozco, & Rangel‐Mendez, ). Adsorbent functionalized with aluminum, cerium, lanthanum and zirconium are more capable of removing contaminants (He et al, ; Lin, Wu, Khayambashi, Wang, & Wei, ; Te, Wichitsathian, Yossapol, & Wonglertarak, ). Some special characteristics such as surface area, porosity and the presence of functional groups enhanced the adsorption properties (Arcibar‐Orozco, Josue, Rios‐Hurtado, & Rangel‐Mendez, ).…”
Section: Removal Of Arsenic and Fluoride From Contaminated Water/raw mentioning
confidence: 99%
“…Many efforts were taken to remove arsenic from potable waters. Such efforts included using a porous pellet adsorbent with an eff iciency of over 47% (Te ., 2017;2018). In some studies, various sorption materials and introducing iron hydroxide granulates were used as the best sorbent (Daus ., 2004).…”
mentioning
confidence: 99%